Career Decision Making: Role of Family- Peer Belonging, Emotional Regulation and Academic Motivation - Yusra Zaki Aboud; Rommel Al Ali (Decision Making: Applications in Management and Engineering, 2025)
The study aimed to test the influence of family and peer belongings on the career decision-making difficulties through academic motivation and emotional regulation. For this objective, quantitative data were collected from 264 students of Saudi Arabian colleges. Hypothesis results showed that family and peer belongings have a significant impact on emotional regulation and academic motivation. On the other hand, emotional regulation also has a significant impact on career decision-making difficulties. While academic motivation has an insignificant effect on career decision-making difficulties. The study with these findings contributed that strong family and peer support played an integral role in increasing the students ’ emotional and academic motivations, which leads to improved career decision making of students. Therefore, career guidance programs should integrate family peer dynamics and focus on building these psychological strengths to better support students’ choices. Research limitations to explore the new research framework